2010
DOI: 10.1016/j.bpj.2010.07.039
|View full text |Cite|
|
Sign up to set email alerts
|

DnaB Helicase Activity Is Modulated by DNA Geometry and Force

Abstract: The replicative helicase for Escherichia coli is DnaB, a hexameric, ring-shaped motor protein that encircles and translocates along ssDNA, unwinding dsDNA in advance of its motion. The microscopic mechanisms of DnaB are unknown; further, prior work has found that DnaB's activity is modified by other replication proteins, indicating some mechanistic flexibility. To investigate these issues, we quantified translocation and unwinding by single DnaB molecules in three tethered DNA geometries held under tension. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
79
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(95 citation statements)
references
References 45 publications
12
79
4
Order By: Relevance
“…DnaB is highly processive and rapid in vitro without the addition of accessory factors (50,51). In contrast, the eukaryotic replication fork helicase requires the heterohexameric Mcm2-7 complex functioning in coordination with GINS and Cdc45 for processive and rapid unwinding (15,17).…”
Section: Discussionmentioning
confidence: 99%
“…DnaB is highly processive and rapid in vitro without the addition of accessory factors (50,51). In contrast, the eukaryotic replication fork helicase requires the heterohexameric Mcm2-7 complex functioning in coordination with GINS and Cdc45 for processive and rapid unwinding (15,17).…”
Section: Discussionmentioning
confidence: 99%
“…2). The extension of the Betterton and Jülicher (11) model we present in this work points out the importance of considering pause kinetics and can be applied to the quantification of the unwinding mechanism of other NA unwinding motors in which pauses are known to be relevant or are expected to occur during their operation (17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…Our data revealed that pauses strongly modulate the average unwinding rate of the mutant polymerase. Similarly, pauses have been shown also to be part of the unwinding mechanism of several specialized nucleic acid (NA) motors (17)(18)(19)(20). Therefore, the kinetics of pause events must be considered for the correct interpretation of tension and sequence dependencies of the unwinding rates.…”
Section: Inclusion Of Pause Kinetics In a Model To Quantify The Unwinmentioning
confidence: 99%
“…In addition to DNA unwinding, replicative helicases play a key role in coordinating leading and lagging strand synthesis by mediating interactions with the polymerase and primase enzymes (Benkovic et al, 2001; Hamdan and Richardson, 2009; Indiani et al, 2009; Patel et al, 2011b). In isolation, replicative helicases are efficient single-stranded (ss)DNA translocases, but slow at unwinding the duplex DNA relying completely or partly on thermal fraying of the junction base pair (Donmez et al, 2007; Johnson et al, 2007; Kim et al, 2002; Lionnet et al, 2007; Ribeck et al, 2010) However, when the helicase is associated with the replicative polymerase, unwinding occurs at a fast rate (Dong et al, 1996; Kim et al., 1996; Korhonen et al, 2004; Manosas et al, 2012b; Stano et al, 2005). Similarly, replicative polymerases rely on helicases to processively copy the duplex DNA (Kang et al, 2012; Manosas et al, 2012b; Stano et al, 2005).…”
Section: Introductionmentioning
confidence: 99%